PENGARUH PERSEPSI KEMUDAHAN, SOCIAL INFLUENCE DAN PERSEPSI RESIKO TERHADAP MINAT MEMBELI KEMBALI KONSUMEN PADA PLATFORM SOCIAL COMMERCE TIKTOK YANG DIMEDIASI OLEH VARIABEL KEPERCAYAAN - Depi Sri Handayani; Christina Ekawati (Jurnal Manajemen Bisnis Krisnadwipayana, 2025)
This study aims to analyze the role of trust in mediating the influence of perceived ease of use, social influence, and perceived risk on repurchase intention on TikTok Shop, one of the fastest-growing social commerce platforms in Indonesia. The background of this research is the increasing intensity of consumer purchases through live shopping features and short videos, which requires a deeper understanding of the psychological factors influencing user loyalty. The study involved 100 active TikTok Shop users and was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that perceived ease of use and social influence do not significantly affect trust among TikTok Shop users. On the other hand, perceived risk has a negative and significant effect on trust. Furthermore, trust has a positive and significant impact on repurchase intention. Another notable finding is that trust does not mediate the relationship between perceived ease of use and social influence on repurchase intention, but plays a significant mediating role in the relationship between perceived risk and repurchase intention.The implications of these findings suggest that TikTok Shop and its sellers should focus more on managing and reducing consumers’ perceived risks, such as payment security, product authenticity, and seller transparency. Loyalty-building strategies should not only rely on platform usability or influencer promotions but must also emphasize efforts to build trust through consumer protection and secure, reliable transactions.